A Paleolithic Diet with and without Combined Aerobic and Resistance Exercise Increases Functional Brain Responses and Hippocampal Volume in Subjects with Type 2 Diabetes - Stomby, Andreas; Otten, Julia; Ryberg, Mats; Nyberg, Lars; Olsson, Tommy; Boraxbekk, Carl-Johan (Frontiers in Aging Neuroscience, 2017)
Type 2 diabetes is associated with impaired episodic memory functions and increased risk of different dementing disorders. Diet and exercise may potentially reverse these impairments. In this study, sedentary individuals with type 2 diabetes treated by lifestyle ± metformin were randomized to a Paleolithic diet (PD, n=12) with and without high intensity exercise (PDEX, n=12) for 12 weeks. Episodic memory function, associated functional brain responses and hippocampal grey matter volume was measured by magnetic resonance imaging. A matched, but not randomized, non-interventional group was included as a reference (n=6). The PD included a high intake of unsaturated fatty acids and protein, and excluded the intake of dairy products, grains, refined sugar and salt. The exercise intervention consisted of 180 minutes of supervised aerobic and resistance exercise per week. Both interventions induced a significant weight loss, improved insulin sensitivity and increased peak oxygen uptake without any significant group differences. Furthermore, both interventions were associated with increased functional brain responses within the right anterior hippocampus, right inferior occipital gyrus and increased volume of the right posterior hippocampus. There were no changes in memory performance. We conclude that life-style modification may improve neuronal plasticity in brain areas linked to cognitive function in type 2 diabetes. Putative long-term effects on cognitive functions including decreased risk of dementing disorders await further studies.